HEALTH RISK ANALYSIS OF LEAD (Pb) HEAVY METAL CONTENT IN DRINKING WATER IN FLOOD-PRONE AREAS - Fitriani; Syamsul Bahri; Husna Maulida; Muhammad Syahrul Manzili; Faiza Humaira (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2025)
Floods are hydrometeorological disasters that have the potential to reduce drinking water quality through the mobilization of environmental pollutants, including heavy metals such as lead (Pb). This study aims to analyze lead content in drinking water and assess the level of public health risks due to exposure through the ingestion pathway. The study uses an environmental health risk analysis approach by calculating non-carcinogenic intake (Ink) and Risk Quotient (RQ) based on the rate of water consumption, duration of exposure, frequency of exposure, and body weight of respondents. The research method uses a descriptive survey with a cross-sectional approach conducted in Peunayan Village, Nisam District, North Aceh Regency. The research sample consisted of 50 respondents with a random sampling technique. The results showed that the lead concentration was 0.0010 mg/L and this value is still below the maximum limit stipulated in the Regulation of the Minister of Health of the Republic of Indonesia Number 492/MENKES/PER/IV/2010, which is 0.01 mg/L for lead parameters in drinking water. The calculation of non-carcinogenic intake showed a real-time value of 0.000053 mg/kg/day with a Risk Quotient (RQ) of 0.014, indicating that non-carcinogenic health risks are still in the safe category (RQ≤1). Long-term exposure projections showed an increase in intake and RQ values to 0.67 in the 50-year estimate, but remained below the risk limit. These findings indicate that although lead concentrations still meet safety standards, the potential for long-term exposure accumulation requires attention. Therefore, regular water quality monitoring, public education, and the implementation of simple water treatment technologies are important steps in preventing environmental health risks